Zone 2 arch repair for acute type A dissection: Evolution from arch-first to proximal-first repairCentral MessagePerspective - Suguru Ohira, MD, PhD; Vasiliki Gregory, MS; Joshua B. Goldberg, MD; Ramin Malekan, MD; Igor Laskowski, MD; Corazon De La Pena, MD; Steven L. Lansman, MD, PhD; David Spielvogel, MD; Masashi Kai, MD (JTCVS Techniques)
Objective: With growing experience of acute type A aortic dissection repair, Zone 2 arch repair has been advocated. The aim of this study is to compare the outcome between “proximal-first” and “arch-first” Zone 2 repair. Methods: From January 2015 to March 2023, 45 patients underwent Zone 2 arch repair out of 208 acute type A aortic dissection repairs: arch-first, N = 19, and proximal-first technique, N = 26, since January 2021. Indications were aortic arch or descending tear, complex dissection in neck vessels, cerebral malperfusion, or aneurysm of the aortic arch. Results: The lowest bladder temperature was higher in the proximal-first technique (24.9 °C vs 19.7 °C, P < .001). Cardiopulmonary bypass (230 vs 177.5 minutes, P < .001), myocardial ischemic (124 vs 91 minutes, P < .001), and lower-body circulatory arrest (87 vs 28 minutes, P < .001) times were shorter in the proximal-first technique. The arch-first group required more packed red blood cells (arch-first, 2 units vs proximal-first, 0 units, P = .048), platelets (arch-first, 4 units vs proximal-first, 2 units, P = .003), and cryoprecipitates (arch-first, 2 units vs proximal-first, 1 unit, P = .024). Operative mortality and major morbidities were higher in the arch-first group (57.9% vs 11.5%, P = .001). One-year survival was comparable (arch-first, 89.5% ± 7.0% vs proximal-first, 92.0% ± 5.5%, P = .739). Distal intervention was successfully performed in 5 patients (endovascular, N = 3, and open repair, N = 2). Conclusions: Zone 2 arch repair using the proximal-first technique for acute type A aortic dissection repair yields shorter lower-body ischemic time with a warmer core temperature, resulting in shorter cardiopulmonary bypass time, less blood product use, and fewer morbidities when compared with the arch-first technique.